Effects of fungal treatments on chemi-mechanical pulp and paper properties from hornbeam wood - Jafar Ebrahimpour Kasmani (Regional Information Center for Science and Technology (RICeST), 2012)
The strength properties of paper produced from pulp obtained after 1, 2 and 4 weeks treatment of hornbeam chips with the Phanerochaete chrysosporium BKM - 1767 fungus was evaluated and compared with control samples. After preparing fungal specimens, hornbeam chips were exposed to this fungus for one of the three periods of 1, 2 and 4 weeks at 39oC temperature and 65% relative humidity. Then CMP pulp was prepared using treated chips, chemical treatment temperature of 165oC, for either 80 or 90 minutes and sodium sulfite charge of 14, 18 and 22% (based on oven dry weight of the wood).  The liquor to chips was constant at 7 to 1. The results showed that the CMP pulping yield from treated chips was lower than control sample and the reduction after treatments for 1, 2 and 4 weeks was  almost 1.64, 2.84, 6.20 percent respectively. Also the strength indices of paper such as tensile strength, burst strength, tear strength and folding endurance paper prepared from treated chips were lower than control chips